Desafios da docência no ensino superior: o caso do curso de publicidade e propaganda - Nocetti, Isabela Wippich Jorge (2015)
This research aims to infer the National Curriculum Guidelines of the Social Communication course with specialization in Publicity and Advertising and pedagogical projects, challenges of teaching in university education. The intention was to highlight challenges for teaching practice in Publicity and Advertising courses and discuss them as a reference to the utterances of teachers who work in these courses. For the development of the research we used Masetto¿s studies (1998, 2003 and 2013), Cunha¿s (1989, 2001, 2007 and 2010), Tardif¿s (2005), Roldão¿s (2005 and 2007), Pimenta¿s (2002 and 2011), Isaia¿s (2006), Anastasiou¿s (2004) among others. There was a qualitative study and the methodology included as an information source the National Curriculum Guidelines, the documents describing the educational projects of both institutions and the responses given by three professors interviewed who work in Publicity and Advertising courses and in different private universities, located in Santos. The main challenges listed were: a change in the profile of entering students; the requirements of complexity of contemporary world; the relationship between theory and practice; teaching practices that promote creativity and the use of new languages by the student and, finally, the social responsibility of the profession and the ethical commitments. The study resulted in some considerations in relation to university education student profile, to information of access facilities, the teaching practices in the course of Publicity and Advertising and the identity construction process of the higher education teacher. It was discussed that to confront the challenges facing the practice of teaching in higher education is essential to overcome the culture of individualism. It highlights the role of higher education institutions in creating systematic formative spaces that foster the professional development learning to teach, which implies consider the opinions of teachers and, above all, listen to them talk about the problems they face in teaching practice. Continuing education processes in higher education should also consider other aspects such as attention to the climate of collaboration between teachers as well the support and the presence of the necessary resources to innovation. It was considered that overcoming the isolation of teaching is the essential condition for institutions to show the most advanced and consistent propositions in their formative projects.